Makna Denotasi dan Konotasi Dalam Novel 127 Days Karya Nadzira Shafa - Sinta; Desty Endrawati Subroto; Mahpudoh (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research is motivated by the importance of understanding denotative and connotative meanings in literary works, particularly novels, to understand the messages conveyed directly and implicitly. This study aims to describe the denotative and connotative meanings in the novel "172 Days." This study employed a qualitative descriptive method with a semantic approach. Data collection utilized reading and note-taking techniques. Data in the form of words, phrases, and sentences containing denotative and connotative meanings were analyzed based on Roland Barthes' semiological theory through the stages of identification, classification, and interpretation of meanings according to their context. The results show that Nadzira Shafa's novel "172 Days" contains forms of denotative and connotative meanings found in words, phrases, and sentences within the context of the story. Thus, the study of denotative and connotative meanings provides a deeper understanding of the messages contained in the novel "172 Days."